Gallic Acid and Cyclosporine Mixture and their Effects on Cardiac Dysfunction Induced by Ischemia/Reperfusion and eNOS/iNOS Expression - Badavi,Mohammad (2017)
Abstract Background: Although many researches have been conducted on either a certain antioxidant or mPTP individually, little attention has been drawn to the effects of co-administration of an antioxidant and mPTP inhibitor together on cardiac dysfunction after I/R injury. Objectives: This study aims at determining the effects of gallic acid (as Antioxidant) combined with cyclosporine A (CsA) (as mPTP inhibitor) on I/R induced cardiac and endothelial (role of NO) dysfunction. Methods: Male Wistar rats were pretreated with gallic acid (7.5, 15, or 30 mg.kg-1 body weight, daily) for a period of 10 days. Then, the heart was isolated and exposed to 30-minute ischemia and perfused by CsA (0.2 µM) 20 min during reperfusion period. Results: The data have shown that infarct size was decreased significantly by CsA and gallic acid alone (p < 0.05, one way ANOVA followed by LSD test), however the combination of both drugs had more significant improving effects (p < 0.001). The combination of these two drugs improved more significantly maximum rate of rise and fall of ventricular pressure (±dp.dt-1 max), rate pressure product (RPP), left ventricular developed pressure (LVDP), heart rate and coronary flow rather than applying each one alone (p < 0.05, repeated measurement ANOVA followed by LSD test). Conclusions: In conclusion, benefiting from an antioxidant concomitant with an mPTP inhibitor could have more improving effects on the cardiac dysfunction induced by I/R injury.